Identification of diverse BoLA DQA3 genes consistent with non-allelic sequences - Ballingall, Keith T.; Marasa, B.S.; Luyai, A.; McKeever, Declan J. (Wiley, 1998)
Previous analysis of the second exon sequences derived from genomic DQA3 genes of the MHC in cattle identified 2 distinct families, DQA3*01 and DQA3*02. In this paper, the nucleotide and predicted amino acid sequences of the entire coding region of 3 transcribed DQA3 genes representing each of these families are described. The results provide additional evidence that the DQA3 locus is distinct from DQA1 and DQA2. The amino acid sequence of DQA3 genes from the 2 gene families differed by 35 out of the 254 amino acids. Putative locus-specific amino acid sequence motifs within the transmembrane and intracytoplasmic domains of DQA genes differed between the DQA3*01 and DOA3*02 genes. A phylogenetic analysis revealed that the genetic distance between families represented by DQA3*01 and DQA3*02 was considerably larger than that between orthologous MHC allelic families. The results are consistent with an extremely divergent family of DQA3 genes or an allele at an additional DQA4 locus. The nucleotide sequences reported in this paper have been assigned accession numbers Y14020-Y14022.